Britain, the EEC, and the Third World : report of an international conference jointly sponsored by the Society for International Development and the Overseas Development Institute at the Royal Society, April 26-27, 1971 - Campbell, John Middleton, Baron Campbell of Eskan; Society for International Development; Overseas Development Institute (London, England) (New York : Praeger Publishers, 1972)
The purpose of the conference was, first, to improve understanding of the institutions and policies relating to developing countries of the United Kingdom on the one hand and the EEC on the other; second, to judge and compare the good and the less good qualities of each, with a view to ensuring that harmonization of policies would be so far as possible on the basis of their highest common factor; and third, to make progress in clarifying and defining particular problem areas and countries
osc 21/11/2018
Loans
Keywords: Developing countries